Ultrasound-Promoted and Base-Mediated Regioselective Bromination of Imidazo[1,2-a]pyridines with Pyridinium Tribromide - Jiang, Hongmei; Guo, Dingyi; Zhang, Yixin; Shen, Qin-Peng; Tang, Shiyun; You, Junheng; Huo, Yi; Wang, Huixian; Gui, Qing-Wen (Synthesis, 2020)
By using pyridinium tribromide as the bromo source, an efficient and practical protocol for the synthesis of C3-brominated imidazo[1,2-a]pyridines through ultrasound-promoted and Na2CO3-mediated regioselective bromination of imidazo[1,2-a]pyridines has been developed. This method effectively avoids the use of metal catalysts and harsh reaction conditions, and shows attractive characteristics such as operational simplicity, broad substrate scope with good to excellent yields, ease of scale-up and high energy efficiency.
Keywords: bromination; pyridinium tribromide; metal-free synthesis; regioselectivity; imidazopyridines; ultrasonic irradiation; base mediated